Genetic enhancement of mustard for seed yield & its sustainability - Dhiraj Singh (Journal of Oilseed Brassica, 2026)
The contribution of rapeseed-mustard to the totaloilseed acreage and production in India is 23.7%and 26% respectively, during the year 2012-13. Theyield of rapeseed-mustard was 1176 kg/ha ascompared to 955 kg/ha of total oilseeds. Indianmustard (Brassica juncea (L.) Czern & Coss.)accounts for about 80 % of the 6.3 m ha area underrapeseed- mustard crops in the country